Evaluation on the antiviral activity of genipin against white spot syndrome virus in crayfish - Huang, Ai-Guo; Tan, Xiao-Ping; Qu, Shen-Ye; Wang, Gao-Xue; Zhu, Bin (Fish & shellfish immunology, 2019)
White spot syndrome virus (WSSV) is a serious epidemic pathogen of crustaceans and cause severe economic losses to aquaculture. However, no commercial drugs presently available to control WSSV infection. Genipin (GN) is a bioactive compound extracted from the fruit of Gardenia jasminoides and exhibits potential antiviral activity. In the study, the antiviral activity of GN against WSSV was investigated in crayfish Procambarus clarkii and in shrimp Litopenaeus vannamei. In vitro antiviral test showed that GN could inhibit WSSV replication in crayfish and in shrimp, and the highest inhibition on WSSV was over 99% when treatment with 50 mg/kg of GN for 24 h. In vivo antiviral test proved that GN could be used to treat and prevent WSSV infection. GN could also effectively protect crayfish from WSSV infection by reducing the mortality rate of WSSV-infected crayfish. Moreover, GN attenuated the WSSV-induced oxidative stress and inflammatory by upregulation the expression of antioxidant-related genes and downregulation the expression of inflammatory-related genes, respectively. Mechanically, GN inhibited WSSV replication at least via decreasing STAT (signal transducer and activator of transcription) gene expression to block WSSV immediate-early gene ie1 transcription. Additionally, the inhibition of BI-1 (Bax inhibitor-1) gene expression also played an important role in the suppression of WSSV infection. In conclusion, GN represented a potential therapeutic and preventive agent to block WSSV infection. •Genipin inhibits WSSV replication in crayfish and in shrimp.•Genipin reduces the mortality rate of WSSV-infected crayfish.•Genipin has anti-oxidative and anti-inflammatory activities in crayfish.•Genipin inhibits the expression of STAT to block the transcription of WSSV immediate-early gene ie1.